2015
DOI: 10.1002/app.43067
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient dispersant from black liquor for carbendazim suspension concentrate: Preparation, self‐assembly behavior and investigation of dispersion mechanism

Abstract: Compared with traditional approaches using synthetic amphiphilic block copolymers, alkyl chain cross-linked lignosulfonate (ASL) with high molecular weight (Mw) from black liquor was synthesized and characterized by GPC, functional group content, FTIR, and 1 H-NMR measurement, and then used as water soluble amphiphilic biopolymer to prepare polymersomes via solution self-assembly. DLS illustrated the solution assembly behavior. The hollow nature of nanospheres was revealed by TEM. Moreover, the element analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Recently, the output of enzymatic hydrolysis lignin (EHL, a byproduct of biorefinery) has exhibited yearly increases due to the development of the biomass refining industry. Most notably, when amphiphilic lignin molecules are dissolved in a selective solvent, microscopic phase separation occurs with subsequent self-assembly to form particles with a core–shell structure, which provides a simple and feasible path for the high value application of EHL [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the output of enzymatic hydrolysis lignin (EHL, a byproduct of biorefinery) has exhibited yearly increases due to the development of the biomass refining industry. Most notably, when amphiphilic lignin molecules are dissolved in a selective solvent, microscopic phase separation occurs with subsequent self-assembly to form particles with a core–shell structure, which provides a simple and feasible path for the high value application of EHL [5].…”
Section: Introductionmentioning
confidence: 99%
“…S1). 33 In Table 1, the contents of nitrogen (N) in the surface and whole of EB@PGA 33 were 9.964% and 9.235%, respectively. The N content of EB of 1.389% accounted for a very small part of the total content.…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that the surface wettability of CD-LHNP with the gold sheet was better, which was favorable for spreading on the surface of the gold substrate. Tetrahydrofuran was used as a good solvent and water was used as a poor solvent to prepare the nanoparticles so hydrophilic chains of lignin would aggregate on the nanoparticles’ shell due to the hydrophobic effect [29]. When β-cyclodextrin was conjugated with EHL, the ratio of hydrophilic groups on the molecular chain was increased, leading to a lower surface contact angle of CD-LHNPs after self-assembly.…”
Section: Resultsmentioning
confidence: 99%